Inflammatory Bowel Disease in Patients with Congenital Chloride Diarrhoea. (26th March 2021) - Norsa, Lorenzo; Berni Canani, Roberto; Duclaux-Loras, Remi; Bequet, Emeline; Köglmeier, Jutta; Russell, Richard K; Uhlig, Holm H; Travis, Simon; Hollis, Jennifer; Koletzko, Sibylle; Grimaldi, Giusi; Castaldo, Giuseppe; et al.
Abstract: Background: Congenital chloride diarrhoea [CLD] is a rare autosomal recessive disease caused by mutations in the solute family carrier 26 member 3 [ SLC26A3 ] gene. Patients suffer from life-long watery diarrhoea and chloride loss. Inflammatory bowel disease [IBD] has been reported in individual patients with CLD and in scl26a3 -deficient mice. Methods: We performed an international multicentre analysis to build a CLD cohort and to identify cases with IBD. We assessed clinical and genetic characteristics of subjects and studied the cumulative incidence of CLD-associated IBD. Results: In a cohort of 72 patients with CLD caused by 17 different SLC26A3 mutations, we identified 12 patients [17%] diagnosed with IBD. Nine patients had Crohn's disease, two ulcerative colitis and one IBD-unclassified [IBD-U]. The prevalence of IBD in our cohort of CLD was higher than the highest prevalence of IBD in Europe [ p < 0.0001]. The age of onset was variable [13.5 years, interquartile range: 8.5–23.5 years]. Patients with CLD and IBD had lower z-score for height than those without IBD. Four of 12 patients had required surgery [ileostomy formation n = 2, ileocaecal resection due to ileocaecal valve stenosis n = 1 and colectomy due to stage II transverse colon cancer n = 1]. At last follow-up, 5/12 were on biologics [adalimumab, infliximab or vedolizumab], 5/12 on immunosuppressants [azathioprine or mercaptopurine], one on 5-ASA and one off-treatment. Conclusions: A substantial proportion of patients with CLD develop IBD. This suggests the potential involvement of SL26A3-mediated anion transport in IBD pathogenesis. Patients with CLD-associated IBD may require surgery for treatment failure or colon cancer.